ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI BRAND AMBASSADOR TERHADAP PURCHASE INTENTION PRODUK SKINCARE DENGAN TRUST SEBAGAI VARIABEL INTERVENING PADA GENERASI Z - Jessy, Jessy (Media Bina Ilmiah, 2024)
One of the developments that has become a trend in the current era is the trend of beauty and skin care. The group that dominates in skin care and beauty is Generation Z. This research aims to identify and analyze factors that influence purchase intentions of local skin care products branded by Korean celebrities. The object of this research is generation Z in Batam City who have purchased local skincare products that use Korean celebrities as brand ambassadors. Data analysis used in this research was carried out using Smart PLS with a total of 348 respondents. The research results show that the variables brand awareness, information quality and usefulness have a significant positive effect on trust, while the variables electronic-word of mouth and reputation do not have a significant effect.